2010
DOI: 10.1016/j.cub.2009.12.053
|View full text |Cite
|
Sign up to set email alerts
|

Armus Is a Rac1 Effector that Inactivates Rab7 and Regulates E-Cadherin Degradation

Abstract: Our data indicate that active Rac1 recruits Armus to locally inactivate Rab7 and facilitate E-cadherin degradation in lysosomes. Thus, the integration of Rac1 and Rab7 activities by Armus provides an important regulatory node for E-cadherin turnover and stability of cell-cell contacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
124
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(127 citation statements)
references
References 40 publications
3
124
0
Order By: Relevance
“…The nucleotide cycle of this Rab is regulated by the GTPase-activating proteins (GAPs) TBC1D15 (Zhang et al, 2005) and TBC1D2 (also known as Armus) (Frasa et al, 2010), and the GEF complex Mon1-Ccz1 (Nordmann et al, 2010). The homotypic fusion and protein sorting (HOPS) complex functions as a Rab7 GEF in yeast (Wurmser et al, 2000), and overexpression of some of the HOPS subunits causes perinuclear clustering of lysosomes in mammalian cells (Wurmser et al, 2000;Poupon et al, 2003).…”
Section: Retrograde Transportmentioning
confidence: 99%
“…The nucleotide cycle of this Rab is regulated by the GTPase-activating proteins (GAPs) TBC1D15 (Zhang et al, 2005) and TBC1D2 (also known as Armus) (Frasa et al, 2010), and the GEF complex Mon1-Ccz1 (Nordmann et al, 2010). The homotypic fusion and protein sorting (HOPS) complex functions as a Rab7 GEF in yeast (Wurmser et al, 2000), and overexpression of some of the HOPS subunits causes perinuclear clustering of lysosomes in mammalian cells (Wurmser et al, 2000;Poupon et al, 2003).…”
Section: Retrograde Transportmentioning
confidence: 99%
“…The activity of small GTPases is modulated by GAPs and guanine nucleotide exchange factors (GEFs) (Fukuda, 2011). Armus has been reported as a Rab7 GAP with a putative PH domain that could mediate PI(3)P binding (Frasa et al, 2010;Lemmon, 2003). Therefore, it is possible that Armus is recruited to PI(3)P-positive structures to promote Rab7-GTP hydrolysis.…”
Section: The Rab7 Gap Armus Is a Pi(3)p-binding Proteinmentioning
confidence: 99%
“…4C). Armus subcellular localization can vary between cells but intracellular puncta are present in epithelial cells (Frasa et al, 2010). Owing to the lack of reliable antibodies for endogenous proteins, we overexpressed MycArmus and Flag-Rab7 in HeLa cells and observed that Armus and Rab7 colocalized ( Fig.…”
mentioning
confidence: 99%
“…In Fig. 1D, the expression of the GAP domain of Armus (Armus-GAP; Armus is also known as TBC1D2A) (Frasa et al, 2010) decreased the FRET/ CFP ratio in a dose-dependent manner. The expression of both Mon1a and Ccz1 with Armus-GAP (Fig.…”
Section: Development Of a Sensor For Rab7 Activitymentioning
confidence: 99%
“…The cDNA for a GAP domain of Armus (a gift from Vania M. Braga, Imperial College, London, UK; Frasa et al, 2010) was subcloned into the pCAGGS expression vector. The cDNAs for mouse Mon1a and Ccz1 were obtained by conventional PCR techniques (Fukuda et al, 1999) and subcloned into pEGFP-C1 (Clontech, Mountain View, CA).…”
Section: Plasmidsmentioning
confidence: 99%